CircITSN1/EIF4A3/Itsn1 axis mediates postoperative cognitive dysfunction in aged mice: A novel mechanism and therapeutic target - Changteng Zhang; Xiaoyu Zhu; Rui Gao; Hai Chen; Caiyi Yan; Wangyang Liu; Lina Yang; Xianzheng Zeng; Haoran Yang; Jin Liu; Qi Li; Daqing Ma; et al. (Molecular Therapy: Nucleic Acids)
Circular RNAs (circRNAs) are stable noncoding RNAs that play a crucial role in neurodegenerative diseases, and they have been implicated in the pathogenesis of postoperative cognitive dysfunction (POCD). However, their underlying molecular mechanisms in POCD remain poorly understood. This study identified hsa_circRNA_061570 as significantly upregulated in plasma after anesthesia/surgery using high-throughput circRNA microarray screening, correlating with cognitive decline. Its murine homolog, circITSN1, was further investigated using shRNA-mediated knockdown in the hippocampus. Behavioral tests (open field, Y maze, and fear conditioning) revealed that circITSN1 suppression improved spatial and contextual memory without affecting motor function. Neuronal damage analysis via Golgi staining demonstrated that circITSN1 knockdown alleviated synaptic and dendritic spine impairments. Mechanistically, circITSN1 directly bound to RNA-binding protein EIF4A3, stabilizing Itsn1 mRNA and activating the JNK inflammatory pathway, thereby increasing pro-inflammatory cytokines. Spatial co-localization of circITSN1 with neuronal markers and EIF4A3 underscored its neuron-specific regulatory role. These findings establish circITSN1 as a critical mediator of neuroinflammation through JNK pathway activation, positioning it as both a diagnostic biomarker and a promising therapeutic target for POCD intervention. The study bridges circRNA biology with neurocognitive pathology, offering novel insights into post-surgical cognitive impairment mechanisms.